Conceptual and Applied Changes in the Approach to Well-being at School- Systematic Literature Review - Katalin BORBÁTH; Attila Czabaji HORVÁTH (Revista de Știinţe Educaţiei, 2024)
This paper attempted to outline the interdisciplinary and broad path of well-being until it became a goal in the Learning Compass. The work paid special attention to positive psychology because they agreed that its insights need to be translated into positive pedagogy for the well-being of learners. So, it offers a collection and comparison of the main well-being concepts from different disciplines connected to the learning environment's psychological pedagogical, social, and economic aspects, using the systematic literature review as methodology. The paper also focuses on examples of studies of the concept of well-being, narrowing step by step to the psychological, especially the social and the subjective well-being concepts. It is proven that student well-being is closely linked to the wellbeing of teachers, and therefore supporting the subjective/psychological, and professional/ wellbeing of teachers is essential for the quality learning-teaching process and for achieving the 2030 target summarized in the Learning Compass.